(untitled) (Revista cientifica In Vestigium Ire, 2019)
The research labor can be understood as a way to know reality, in this sense, the dissemination of information and the results of research processes, become an essential task for the appropriation of knowledge and Access to the production culture of the same. Nowadays, scientific literacy is a necessity, as it allows the development of a true critical thinking, making possible the understanding of technical and scientific language, which in many cases is unachievable for most people. The knowledge, information and communications society, must seek students with creative and critical thinking (Martínez Armesto, 1997) in addition to training in values and ethical commitments. The foregoing implies that access, by the majority of the population, to a scientific and technological culture, makes it easier to understand the world around us in a critical manner and, in addition, provides tools for a more democratic participation in social interest issues. Research and divulgation cannot be separated from one another, because while the former seeks to reinforce concepts or theories, relying on methodologies of scientific rigor; The dissemination, meanwhile, seeks to express the results and hypotheses, supported by language tools , accessible to citizens of different nationalities. Thus, in this context, the magazine In Vestigium Ire intends to be a bridge for the integration of scientific knowledge in economic, administrative and accounting areas; and the community in general, making known the findings, fruit of the investigative processes. In this opportunity, results of research works related to environmental sustainability, competitiveness and development of the regions, leadership and social entrepreneurship, as well as management issues related to the accounting part, are presented. We trust that our readers will find in these articles, great contributions to the construction of knowledge and at the same time can combine efforts to motivate the incursión in the investigative work, as expressed by Martin Bonfil Olivera "there is an undeniable need to have researchers who do science, seek answers to new and old enigmas."